Analisis Efisiensi Dan Produktivitas Penerapan Sistem Rubber track Pada Tractor Cultivator - Rizky Maulana; Dani Mardiyana; Oscar Haris (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
Soil cultivation is carried out by utilizing human power, utilizing animal power, and using tools such as hoes to equipment that uses machine power, one of the tools to carry out activities such as land cultivation is a tool called a cultivator . The conventional cultivator has several drawbacks when it comes to tilling the soil, namely the wheel needs to be replaced with a rotary then the operator holds the handle while walking behind the cultivator to do the tillage. The method of this research is to modify the cultivator with a rubber track design using the autodesk inventor application and efficiency analysis on the cultivator as well as calculating the comparison between hoes, conventional cultivator s and also modified cultivator s by comparing the time needed to cultivate the land with a land area of 1 Ha. The results on the rubber track system are more efficient and more productive because the time required for tillage with a land area of 1 ha only takes 8.47 hours while the hoe takes 167.33 hours and conventional cultivator takes 9.09 hours.